SCREENING OF BIOACTIVE COMPOUNDS FROM UNKNOWN MARINE SPONGES COLLECTED FROM KOVALAM, CHENNAI - Thambidurai, Yuvarani; D, Sudarsanam; Habeeb Skm; Kizhakudan, Joe k (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study is designed to hunt for the presence of bioactive compounds from three marine sponges collected from Kovalam. Methods: Zoochemical analysis is performed to screen for the presence of secondary metabolites. Based on those results, only two sponges which showed a significant presence of secondary metabolites has been subjected to gas chromatography-mass spectrometry (GC-MS) analysis to identify the unknown chemical compounds present in those sponges. Results: On analyzing the results, two sponges, namely, Dysidea herbacea and Sigmadocia pumila, has shown a significant presence of secondary metabolites while the third sponge Acanthella elongata have shown moderate presence of secondary metabolites. Since the first two sponges results are remarkable, these two samples have been subjected to GC-MS analysis to separate and identify the unknown chemical compounds present in the sample. Conclusion: Samples, namely, D. herbacea and S. pumila, indicated the presence of several components. From both the sponges, eleven different secondary metabolites were identified by GC-MS. Most of these compounds are widely used in cosmetic, pharmaceutical, and other industries and therefore a vital source for industrial biotechnology and related products in healthcare and skincare. Â 